2023
DOI: 10.3390/min13080996
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution and Passivation Mechanism of Chalcopyrite during Pressurized Water Leaching

Abstract: In this study, chemical leaching, XRD, SEM, and XPS analyses were conducted to investigate the dissolution and passivation mechanisms of chalcopyrite under pressurized oxidative conditions in water. The chemical leaching results showed that the chalcopyrite could be dissolved by pressurized leaching without any acid addition, i.e., in an O2–H2O system, and the copper leaching rate reached 96.4% under the optimal conditions of 180 °C, 1.5 MPa, 900 rpm, and 90 min. The XRD, SEM, and XPS data suggested that a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…Covellite is indicated to be the most stable copper sulphide, being the end product derived from various copper sulphide minerals as discussed by Muszer et al [17]. These researchers also demonstrated covellite persists as an intermediate product during pressure oxidation of a mixed sulphide concentrate in 120 g/L sulphuric acid at 180 • C with oxygen partial pressure of 5 atm for beyond 4 h, albeit at a moderate stirrer speed of 400 rpm, similar to the finding of Jiang et al [15]. Furthermore, covellinisation of copper sulphide minerals does not hinder copper extraction at temperatures of 160 • C and below: using a synchrotron technique, Majuste et.…”
Section: Reaction Of Chalcopyrite With Acidsupporting
confidence: 75%
See 2 more Smart Citations
“…Covellite is indicated to be the most stable copper sulphide, being the end product derived from various copper sulphide minerals as discussed by Muszer et al [17]. These researchers also demonstrated covellite persists as an intermediate product during pressure oxidation of a mixed sulphide concentrate in 120 g/L sulphuric acid at 180 • C with oxygen partial pressure of 5 atm for beyond 4 h, albeit at a moderate stirrer speed of 400 rpm, similar to the finding of Jiang et al [15]. Furthermore, covellinisation of copper sulphide minerals does not hinder copper extraction at temperatures of 160 • C and below: using a synchrotron technique, Majuste et.…”
Section: Reaction Of Chalcopyrite With Acidsupporting
confidence: 75%
“…This conclusion is not contradicted by the results of this, and the previous study [1]. In comparison, the recent study of Jiang et al [15] reported chalcopyrite leaching (with no added acid) conducted at 160-180 • C, typically with a total pressure of 1.5 MPa (including partial pressure of oxygen), no suggestion for phases that could inhibit the reaction. This conclusion was based upon XPS analysis of leach residues generated when the agitation speed in their reactor was 700 rpm (or greater); at lower agitation speeds the reaction of chalcopyrite was slower and significant amounts of covellite intermediate could be detected.…”
Section: Effect Of Added Sulphuric Acidsupporting
confidence: 51%
See 1 more Smart Citation